Lung density on high resolution computer tomography (HRCT) reflects degree of inflammation in smokers - Karimi, Reza (BioMed Central, 2014)
BACKGROUND: Smokers have increased cell concentration in the lower respiratory tract indicating a chronic inflammatory state, which in some individuals may lead to development of chronic obstructive pulmonary disease (COPD). Computer tomography (CT) imaging provides means of quantifying pulmonary structure and early signs of disease. We investigated whether lung density on high resolution CT differs between smokers and never-smokers and if this were associated to intensity of inflammation. METHODS: Forty smoking volunteers with normal pulmonary function, 40 healthy never-smokers and 40 patients with COPD of GOLD stage I-II, were included. Mean lung attenuation and percentage of pixels in the lung with attenuation between −750 and −900 HU (percentage higher density spectrum (%HDS)) were calculated on inspiratory CT-scans. Markers of systemic inflammation in blood and cell counts in bronchoalveolar lavage (BAL) fluid were recorded. RESULTS: Lung density expressed as %HDS was increased in smokers (44.0 ± 5.8%) compared to both never-smokers (38.3 ± 5.8%) and patients with COPD (39.1 ± 5.8%), (p < 0.001, for both). Females had denser lungs than males, which was dependent on body height. Cell concentration in BAL were correlated to lung density in smokers (r = 0.50, p < 0.001). CONCLUSIONS: Lung density on CT is associated with cell concentration in BAL in smokers and may mirror an inflammatory response in the lung. Gender difference in lung density is dependent on height. In COPD with emphysema, loss of lung tissue may counterbalance the expected increase in density due to inflammation. The findings may help to interpret high resolution CT in the context of smoking and gender and highlight the heterogeneity of structural changes in COPD.